Blockage detection in pipelines based on linear frequency modulated acoustic reflection method - Haiyuan Yao; Dan Li; Yan Li; Bo Yang; Yang Meng (Developments in the Built Environment)
Hydrate-induced pipeline blockages pose critical risks to energy infrastructure reliability and operational safety. This study proposes a novel acoustic-based structural health monitoring system integrating linear frequency modulated (LFM) signals with adaptive matched filtering, specifically designed for early blockage detection in complex pipeline networks, including those in built environments. Validated via controlled experiments simulating industrial-scale conditions, the system achieved millimeter-level positioning accuracy (error <1 %) across varying blockage intensities (20–100 %), representing a 40 % precision improvement over conventional methods. The system's capability to resolve multi-stage blockage boundaries enhances predictive maintenance strategies for ensuring energy-efficient pipeline operations and infrastructure integrity management. By enabling real-time identification of incipient hydrate formation phases through acoustic signature analysis, this methodology supports sustainable infrastructure management through timely remedial interventions. Its applicability extends to intelligent building service pipelines, regional energy distribution networks, and deep-sea energy infrastructure, demonstrating significant potential for improving failure prediction and enhancing the resilience of built environment systems.